2013
DOI: 10.1007/s12639-013-0264-y
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of paramphistomosis in sheep and goats in Jammu, India

Abstract: Epidemiology of paramphistomosis in sheep and goats was studied using field and abattoir samples at Jammu, India. Abattoir examination revealed that 36.2 % of sheep and 30.9 % of goats were positive for paramphistomosis. The mean worm counts (±SEM) were 23.5 ± 5.7 in sheep and 19.9 ± 3.5 in goats. On coprological examination, 16.3 % of sheep and 13.6 % of goats were found positive for paramphistomosis. The mean egg counts (±SEM) were 4.4 ± 2.6 in sheep and 3.6 ± 2.1 in goats. Season was found to have a signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
20
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 9 publications
6
20
2
Order By: Relevance
“…In cattle farms, the prevalence of 55.9 % seems to be increasing if compared to the survey carried out in the same region by Scala et al (1997a) 18 years ago, where a prevalence of 19.6 % was found; The values found here are in according to the report of Cringoli et al (2012), (55.7 %), while are lower compared to Spanish (61 %) and Uruguayan (69 %) reports as described by Sanchís et al, (2013). The slaughterhouse's survey revealed a very low prevalence of paramphistomosis in sheep (2 %), similar to fi ndings from Iran (0.041 %) (Tehrani et al, 2015) and Turkey (4.43 %) (Ozdal et al, 2010) but was much lower compared to records from Ethiopia (25 %) (Sissay et al, 2007) and India (36.2 %) (Godara et al, 2014). The lower values obtained from sheep coprological analysis and in slaughterhouse's survey could be probably due to the fact that in this species the infection seems to be less frequent than in cattle (Rojo-Vázquez et al, 2012).…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…In cattle farms, the prevalence of 55.9 % seems to be increasing if compared to the survey carried out in the same region by Scala et al (1997a) 18 years ago, where a prevalence of 19.6 % was found; The values found here are in according to the report of Cringoli et al (2012), (55.7 %), while are lower compared to Spanish (61 %) and Uruguayan (69 %) reports as described by Sanchís et al, (2013). The slaughterhouse's survey revealed a very low prevalence of paramphistomosis in sheep (2 %), similar to fi ndings from Iran (0.041 %) (Tehrani et al, 2015) and Turkey (4.43 %) (Ozdal et al, 2010) but was much lower compared to records from Ethiopia (25 %) (Sissay et al, 2007) and India (36.2 %) (Godara et al, 2014). The lower values obtained from sheep coprological analysis and in slaughterhouse's survey could be probably due to the fact that in this species the infection seems to be less frequent than in cattle (Rojo-Vázquez et al, 2012).…”
Section: Discussionsupporting
confidence: 52%
“…The lower values obtained from sheep coprological analysis and in slaughterhouse's survey could be probably due to the fact that in this species the infection seems to be less frequent than in cattle (Rojo-Vázquez et al, 2012). Regarding cattle, the 10.9 % prevalence found was slightly lower compared to that found about 20 years ago by Scala et al (1997b), (16.9 %) and also compared to French (20 %) (Szmidt-Adjidé et al, 2000) and Spanish (18.8 %) (González-Warleta et al 2013) reports, while were higher compared to the fi ndings reported in Castilla y León, Spain (6.2 %) by Ferreras et al, (2014): indeed these Spanish regions have a very cold and dry climate that may infl uence the parasite life-cycle. The lower prevalence reported in our study could be related to the climate of the region that could affect the biology of the intermediate hosts, compared to other areas with a more humid environmental conditions.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…It is the newly excysted and migratory stages of the parasite that are thought to be responsible for clinical paramphistomosis; a condition regarded as a leading cause of livestock morbidity which results in economic loss in tropical and sub-tropical regions [1,4,8]. Clinical symptoms include lethargy/recumbency, dehydration, severe scour and submandibular oedema, which occur as immature parasites excyst and penetrate the duodenal mucosa causing significant damage to the tissues [9].…”
mentioning
confidence: 99%
“…Parasites then excyst in the duodenum of the small intestine(7)where immature flukes feed on sub-mucosa until they are ready to begin their migration to the rumen. In the rumen, mature fluke attach firmly to the rumen wall, or rumen papillae, via their muscular acetabulum, and release eggs into the rumen contents(8).…”
mentioning
confidence: 99%